Ancient psychoactive substances - Fitzpatrick, Scott M. (Gainesville : University Press of Florida, 2018)
This book details the traditional and sacred use of psychoactive substances by peoples in the ancient past through the lens of archaeology.
Includes bibliographical references and index.
Book Aid International 2021 Donated by Bhutan Society of the UK Trust Fund.
Keywords: Psychotropic drugs -- History; Hallucinogenic drugs -- History; Altered states of consciousness -- History; Hallucinogenic drugs and religious experience -- History; Drug abuse -- History; Alcoholism -- History